The Nature of Divorce in Various Perspectives (Philosophical, Juridical, Sociological, And Psychological Reviews on The Meaning of Divorce) - Nur Hopipah, Eva; Aidah, Yeni; Eva Novita Restu, Cut; Jamarudin, Ade; Saepullah, Usep (PT ARRUS Intelektual Indonesia, 2023)
The essence of divorce has many meanings, depending on the situation and conditions, depending on what perspective it is viewed from. The 4 aspects or perspectives for understanding the nature of divorce analyzed in this study include; (1) the nature of divorce from a philosophical perspective; (2) the nature of the divorce from a juridical perspective; (3) the nature of divorce from a sociological perspective; (4) the nature of divorce from a psychological perspective; (5) the essence of divorce is viewed from the perspective of Islamic law. The results of this research objective are expected to be able to resolve the gaps between various aspects in understanding the nature of divorce. The approach in this study is multidisciplinary in nature so that the data is integral/intact. The research method used is the study of literature with the primary source being the philosophy of Islamic family law, divorce from the perspective of positive law and Islamic law, family psychology, socio-cultural transformation within the family, and other sources that help this research to be comprehensive and used as a secondary source